The Application of Information technology in Libraries in Viet Nam and Requirements for Organisational Models - Nguyễn, Văn Thiên (2020)
This article focuses on the following: systemizing theoretical issues of the impact of ICTs on libraries and issues related to organizational models in ICTs based library environments; Surveying 72 major libraries in Viet Nam in order to gain an understanding of their current status of ICTs applications and the type of organizational models used in those libraries; Interpreting problems that libraries are experiencing, describing the need for changes and requirements for the current organizational models in Viet Nam libraries.